X-Ray Computed Tomography for Failure Mechanism Characterisation within Layered Pouch Cells: Part II : Post-mortem analysis of failed cells. Issue 1 (3rd January 2023) - Patel, Drasti; Reid, Hamish; Ball, Sarah; Brett, Dan J. L.; Shearing, Paul R.
In Part I (1), the failure response of a 1 Ah layered pouch cell with a commercially available nickel manganese cobalt (NMC) cathode and graphite anode at 100% state of charge (SOC) (4.2 V) was investigated for two failure mechanisms: thermal and mechanical. The architectural changes to the whole-cell and deformations of the electrode layers are analysed after failure for both mechanisms. A methodology for post-mortem cell disassembly and sample preparation is proposed and demonstrated to effectively analyse the changes to the electrode surfaces, bulk microstructures and particle morphologies. Furthermore, insights into critical architectural weak points in LIB pouch cells, electrode behaviours and particle cracking are provided using invasive and non-invasive X-ray computed tomography techniques. The findings in this work demonstrate methods by which LIB failure can be investigated and assessed.